PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK CAT TEMBOK AVIAN DI PT.ARTHA JAYA MAS CIWARU KOTA SERANG BANTEN - May Larasati; Jaenudin (Journal of Research and Publication Innovation, 2025)
This study aims to determine the Effect of Price and Promotion on Purchasing Decisions of Avian Wall Paint Products at PT. Artha Jaya Mas Ciwaru, Serang City, Banten. This type of research is quantitative research and the data collection technique used in this study is a questionnaire. The population in this study were all buyers of Avian Wall Paint Products at PT. Artha Jaya Mas Ciwaru, Serang City, Banten with a sample size of 100 respondents. Then an analysis was carried out on the data obtained by classical assumption tests, multiple linear regression, t, F tests, and coefficient tests. Based on the results of the analysis, it shows that the validity and reliability tests of all question items submitted are valid and reliable. The results of the classical assumption test show that this study is normally distributed, there is no multicollinearity, shows heteroscedasticity, and autocorrelation in the regression model. The results of the study show that partially the price has a positive and significant effect on purchasing decisions. This can be seen from the results of the T test, the T count value> T table is 5.183> 1.984 and (sig 0.05). Promotion has a positive and significant effect on purchasing decisions. This can be seen from the results of the T test, the T count value> T table is (11.999> 1.984) and (sig 0.05). Price and Promotion simultaneously have a positive and significant effect on purchasing decisions as seen from the F count value> F table or (76.170> 3.09), this is also reinforced by the ρ value <Sig 0.05 or (0.000 <0.05) with a relationship like this there is a meaning that the better the price and promotion, the more it will increase the Purchase Decision for Avian Wall Paint Products at PT. Artha Jaya Mas Ciwaru, Serang City, Banten.